2015
DOI: 10.1111/jocn.12762
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention and one‐year prognosis of patients following open heart surgery: a randomised clinical trial

Abstract: A well-structured cardiac rehabilitation programme adjusted to the patient's profile is a safe and cost-effective way to improve patients' outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
0
18
1
1
Order By: Relevance
“…We identified two additional relevant papers not included in the 2016 Cochrane review. 28 29 One was excluded because data for our specific research question were not available in a useable format. 28 In total, 22 studies (n=4834 participants) contributed to the analysis ( figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified two additional relevant papers not included in the 2016 Cochrane review. 28 29 One was excluded because data for our specific research question were not available in a useable format. 28 In total, 22 studies (n=4834 participants) contributed to the analysis ( figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 28 29 One was excluded because data for our specific research question were not available in a useable format. 28 In total, 22 studies (n=4834 participants) contributed to the analysis ( figure 1 ). For the study identified from the updated search, 29 there was a low risk of bias in all eight domains, apart from the intention-to-treat analysis, where there was no evidence of this analysis being conducted ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent report, researchers determined that lifestyle counseling that included cardioprotective dietary modifications was effective in reducing cardiac events and increasing the likelihood of positive lifestyle changes among post-coronary artery bypass graft and valvular surgery patients. 88 Increasing evidence suggests that a heart-healthy diet reduces cardiovascular risk not only by favorably modifying lipids, 89,90 blood pressure, body weight, and insulin resistance, but by reducing inflammation as well. 90,91 Independent of statins or weight loss, therapeutic lifestyle changes such as those promulgated by comprehensive CR programs result in substantial reductions in CRP, similar in magnitude to statin therapy.…”
Section: Considerations For Nutrition In Secondary Preventionmentioning
confidence: 99%
“…2 CAD is treated through percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) during the acute phase, and medical management, such as medication and lifestyle modification, is used during the chronic phase. [3][4][5] Despite consistent treatment and management, recurrence of CAD often occurs. Recurrence of CAD is defined differently in each study; the prevalence of recurrent CAD is about 15-50% based on diagnosis confirmed by a cardiologist according to ICD-9 criteria or coronary angiography (restenosis of the coronary artery).…”
Section: Introductionmentioning
confidence: 99%